Still Attached? : Are Social Safety Nets Working? Labor Force Participation in European Regions - Hilgenstock, Benjamin (IMF Working Papers; Working Paper ;, 2018)
The paper examines the evolution and drivers of labor force participation in European regions, focusing on the effects of trade and technology. As in the United States, rural regions within European countries saw more pronounced declines (or smaller increases) in participation than urban regions. Unlike in the United States, however, trade and technology, captured here using novel measures of initial exposures to routinization and offshoring, did not result in detachment from the workforce in European regions. Instead, regions with high initial exposures to routinization and offshoring experienced so-far larger increases in participation, likely driven by an added second worker effect.